Mathematics education in the curricula of the preservice teacher in early childhood education in Spain - Hidalgo-Méndez, María de los Ángeles; León-Mantero, Carmen; Casas-Rosal, José Carlos; Villarraga-Rico, Miguel Ernesto (International Journal of Evaluation and Research in Education (IJERE), 2024)
The objective of this research is to describe the situation of mathematical training in the early childhood education degree curricula in Spain through the analysis of the teaching guides of the subjects with mathematical content offered in the different Spanish universities. The aim is to identify the typology of subjects, the number of subjects offered, and the recommended bibliography. The methodology used is descriptive, exploratory, ex post facto, and census. For this purpose, the registry of universities, centers, and degrees was first consulted during the 2019-2020 academic year to obtain a list of all the Spanish universities that offer degrees in early childhood education and, therefore, to be able to download the corresponding teaching guides. Of the 91 universities in Spain, the early childhood education degree is taught in 66. Likewise, 101 subjects with mathematical content have been identified, although only 99 are available for analysis. Most are compulsory, have a study load of six European credit transfer system (ECTS) credits, and are taught in the third year of the degree. The recommended bibliography mainly concentrates on publications from 2001-2010 and mostly on book references.